Analysis Oil Condition of Transformer PT-8801-A by Using the Method TDCG, Rogers Ratio, Key Gas, and Duval Triangle: A Case Study at PT. Perta Arun Gas - Rastra Furqaranda; Andik Bintoro; Asri Asri; Waleed Khalid Ahmed Al-Ani; Ashish Shrestha (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2022)
The power transformer would have happened disturbanced that can cause a failure at a transformer. For this condition needed to maintenance power transformer, one of which is by analyzing transformer oil by using the TDCG method. This analysis is carried out to determine the diagnosis of faults in the transformer. This method are the condition of the analysis which is based on the amount of a gas dissolved on oil a transformer. This study used four methods for transformer failure analysis are TDCG method, Rogers-ratio, gas key, and duval triangle. The results obtained by the TDCG method of dissolved gas are 1332 ppm, the rogers ratio result a symptom of oil heat a transformer at 300oC, the key gas method results in overheating of oil, and the duval triangle method results in a low breakdown voltage analysis.